Peningkatan Kualitas Pendidikan Dengan Program Manajemen Pemberdayaan Lembaga Pendidikan - Tharaba, M. Fahim; Nur, Muhammad Amin; Mukhlisin, Mukhlisin; Noviyanti, Shobihatul Fitroh; Sanjani, M. Aqil Fahmi (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
The existence of a study program can be part of the solution to problems faced by community members/institutions related to efforts to provide services /guidance/assistance to community members/institutions that are directly related to the scientific development of study programs (1) strengthening the scientific fields of lecturers, students and postgraduate students at UIN Maulana Malik Ibrahim Malang who are multi/inter/transdisciplinary; (2) strengthen the position of study programs in developing education and learning programs based on research for the development of education/non-education in Indonesia. In this study using a participatory action research approach aimed at improving the quality of education with the Educational Institution Empowerment Management Program at the Muslimat Khodijah I Kindergarten, Gondang Pace Nganjuk which aims to determine the increase in the quality of education after empowering educational institutions.. After this research was carried out, the results were obtained: The success of the collaborative recognition activity program for lecturers, students, and students does not only depend on the collaborative team of lecturers, students, and students but depends heavily on the cooperation of all parties involved. Empowerment management of educational institutions (services in Muslimat Khodijah I Kindergarten, Gondang Pace Nganjuk) is realized by participating in activities that are implemented in joint activities, namely Congregational participation, Congregational spiritual coaching, Compensation for orphans from congregations, Departure of Muslimat Khodijah I Kindergarten students, Gondang Pace Nganjuk.